Cerebral Amyloid Angiopathy Is Associated With Higher R2 Relaxation Rate: An MRI and Pathology Study - Md Tahmid Yasar; Arnold M. Evia; Mahir Tazwar; Sue E. Leurgans; David A. Bennett; Julie A. Schneider; Konstantinos Arfanakis (Annals of Clinical and Translational Neurology)
ABSTRACT Objective Cerebral amyloid angiopathy (CAA) involves β‐amyloid deposition in the walls of cortical and leptomeningeal small vessels. Transverse relaxation rate (R2) is a major source of contrast in MRI. This study tested the hypothesis that CAA is associated with R2, extracted the spatial pattern of CAA‐related R2 abnormalities, and evaluated R2 at different CAA severity levels in a large number of community‐based older adults. Methods Cerebral hemispheres from 804 older adults who came to autopsy were included. All hemispheres underwent ex vivo MRI and detailed neuropathologic examination. R2 maps were generated from ex vivo MRI data. Voxel‐wise and region‐based regression analyses were conducted to investigate the association of R2 with CAA, controlling for other neuropathologies and demographics. R2 values at different CAA severity levels were also investigated. Results CAA severity was associated with a higher transverse relaxation rate R2 in cortical and juxtacortical frontal and medial temporal lobe regions, and in deep brain structures, independently of other neuropathologies and demographics. R2 abnormalities were significant in severe CAA, but were limited in terms of spatial extent and magnitude in moderate CAA, and were not detectable in mild CAA. Interpretation This is to our knowledge the first investigation of the link between CAA and R2, one of the major contrast mechanisms in MRI. R2 is sensitive to CAA‐related brain abnormalities, primarily in moderate and severe stages of the disease. In vivo detection of CAA is an important challenge, and the present work contributes new knowledge that may aid toward this goal.